In Vitro Antibacterial Activities of Methanolic Extracts of Fruits, Seeds, and Bark of Zanthoxylum armatum DC. (4th June 2020) - Phuyal, Nirmala; Jha, Pramod Kumar; Raturi, Pankaj Prasad; Rajbhandary, Sangeeta
Abstract : Crude methanol extracts of fruits, seeds, and bark of Zanthoxylum armatum were investigated in vitro for antimicrobial activities against 9 different bacterial strains: Bacillus subtilis, Enterococcus faecalis, Proteus vulgaris, Pseudomonas aeruginosa, Salmonella typhi, Shigella dysenteriae, Staphylococcus aureus, methicillin-resistant Staphylococcus aureus (MRSA), and Staphylococcus epidermidis using agar well diffusion method, and the MBC values were determined. Only 5 bacteria, i.e., Bacillus subtilis, Enterococcus faecalis, MRSA, Staphylococcus aureus, and Staphylococcus epidermidis exhibited antibacterial properties against the different extracts. The fruit and seed extracts showed activities against 5 bacteria, while the bark extract was active against 2 bacteria only (MRSA and Staphylococcus aureus ). Staphylococcus aureus was found to be more susceptible for all the extracts compared to other strains. The maximum ZOI of 20.72 mm was produced by fruits (wild) and 18.10 mm (cultivated) against Staphylococcus aureus. Likewise, the least ZOI of 11.73 mm was produced by seeds (wild) and 11.29 mm (cultivated) against Escherichia faecalis. Similarly, the lowest MBC value of 0.78 mg/mL was obtained for fruit extracts against MRSA, 1.56 mg/mL for fruits, seeds, and bark extracts against Bacillus subtilis, MRSA, and Staphylococcus aureus, and highest value of 50 mg/mL for fruits and seeds extracts against S. epidermidis. The fruits, seeds, and bark extracts of Z. armatum exhibited remarkable antibacterial properties against different pathogenic bacteria causing several diseases, which suggests the potential use of this plant for treating different bacterial diseases such as skin infection, urinary tract infection, dental problems, diarrhea, and dysentery.